Avaliação da atividade relaxante de 17-NOR-subincanadina E, um alcalóide isolado de Aspidosperma ulei MARKGR. sobre a musculatura lisa cavernosa de coelhos - Deocleciano Júnior, Otacilio Benvindo (2008)
Past studies have shown that the indole alkaloidal rich fraction (F(3-5)) from Aspidosperma ulei Markgr. root bark displays pro-erectile function in vivo and a relaxant effect on isolated rabbit corpus cavernosum in vitro. Also, a recent study demonstrated the in vivo pro-erectile like activity of 17-nor-subincanadina E (SEC), an alkaloid isolated from stem bark of this plant. This study aimed to assess further the effect of SEC on the smooth muscle tone (spontaneous or induced) in vitro, utilizing the strips of tracheal, intestinal, vascular and corpus cavernosal tissues of rabbits. An attempt was also made to study the possible mechanism of SEC on rabbit corpus cavernosum (RbCC). RbCC strips, were mounted in organ baths containing Krebs solution. After equilibration, the tissues were precontracted with phenylephrine (10 µM) or potassium (40mM). SEC (1-100 μg/ml) caused a concentration dependent relaxation in the isolated rabbit corpus cavernosum precontracted with phenylephrine and displayed comparatively greater relaxant effect on corpus cavernosum IC50 [7,174 (3,155-16,31) μg/ml], SEC produced concentration-dependent relaxations of the aortic rings in endothelium intact and denuded IC50[29,76 (90,32–115,6) μg/ml] and IC50[ 26,13 (75,83–119,9) μg/ml], respectively, trachea rings IC50[60,25 (0,330-109,8) μg/ml], and of spontaneous motility in segments of duodenum IC50[76,78 (33,09–178,2) μg/ml]. The relaxant effect of SEC (1-100 µg/ml) on phenylephrine contraction was unaffected in the presence of adrenergic blockers (phentolamine and guanethidine), muscarinic blocker (atropine), KATP channel blocker (glibenclamide), Ca2+-dependent K+ channel blockers (apamin and iberiotoxin), and in the presence of N-omega-nitro-L-arginine methyl ester (L-NAME 100 µM)). However, the SEC relaxation was significantly attenuated by ODQ (30 μ M) (79.1%±4.5%, p <0.05). Incubations of RbCC with SEC (10 and 30 µg/mL) caused significant increases of cGMP (21.5%±4.2%, p <0.05) and cAMP (331.95%±26.1%, p <0.05) levels. Preincubation with SEC (10 and 30 µM) also significantly enhanced the relaxation response to the exogenous NO-donor (GTN) and an activator of adenyl cyclase (forskolin). the relaxations evoked by electrical stimulation was significantly decreased by SEC (10 µg/mL) (65.0%±10.9%, p <0.05). The phasic component of the contraction induced by K+ 40 mM as well as the maximal contraction elicited by increasing external Ca2+ concentrations in depolarized corpora cavernosa was inhibited by SEC (15 µg/mL). Our results indicate that SEC can induce comparatively a greater relaxant effect on rabbit cavernosal tissue in vitro via a mechanism that involves an increase of cAMP and cGMP levels and a blocking effect on calcium flux. These data suggest that Aspidiosperma ulei Markgr. can be explored as an alternative for the treatment of erectile dysfunction.